An Exploration of Emergency Physicians' Attitudes Toward Patients With Substance Use Disorder. Issue 2 (March 2018) - Mendiola, Cecelia Kathleen; Galetto, Giorgio; Fingerhood, Michael
Abstract : Objectives: Much is known about some healthcare professionals' attitudes toward patients with substance use disorders, but few studies have specifically looked at emergency department (ED) physicians. Individuals with substance use disorders are more likely to be people who chronically, frequently use the ED, and thus ED physicians are in a unique position to provide early identification and intervention for people struggling with addiction. The purpose of this study was to understand ED physicians' attitudes toward patients with substance use disorder with the aim of decreasing stigma and improving the care of ED patients with substance use disorder. Methods: An anonymous Qualtrics survey was emailed to 115 emergency physicians in the Johns Hopkins Health System. The survey contained (1) demographics and (2) the medical condition regard scale, http://links.lww.com/JAM/A67 . Participants were offered a 10 Amazon gift card to complete the survey. Results: The response rate was 50% (n = 58) and the completion rate was 43% (n = 50). Physicians had lower regard for patients with substance use disorders than other medical conditions with behavioral components. Of note, 54% of respondents indicated that they at least "somewhat agree" that they "prefer not to work with patients with substance use who have pain." Conclusions: A significant portion of our study population had low regard for patients with substance use. Future research is needed to determine significant contributing factors and develop interventions to mitigate negative attitudes among ED physicians toward patients with substance use disorder. Abstract : Supplemental Digital Content is available in the text